1999
DOI: 10.1016/s0735-1097(99)00208-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of microvolt-level T-wave alternans in patients with dilated cardiomyopathy

Abstract: T-wave alternans was closely related to VT in patients with DCM. T-wave alternans is a useful noninvasive test for identifying high risk patients with DCM who have VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 28 publications
0
47
0
1
Order By: Relevance
“…The presence of microvolt-level TWA, measured using the spectral method during bicycle exercise testing, has been reported to be associated with an increased risk of ventricular arrhythmias in several clinical settings, [13][14][15][16][17] and we have reported its clinical usefulness in identifying patients at risk after acute MI. 16 Recently, Klingenheben et al 17 reported that TWA was independently associated with arrhythmic events in congestive heart failure, whereas other noninvasive markers, including LP, were not.…”
Section: Twa and Arrhythmiamentioning
confidence: 89%
“…The presence of microvolt-level TWA, measured using the spectral method during bicycle exercise testing, has been reported to be associated with an increased risk of ventricular arrhythmias in several clinical settings, [13][14][15][16][17] and we have reported its clinical usefulness in identifying patients at risk after acute MI. 16 Recently, Klingenheben et al 17 reported that TWA was independently associated with arrhythmic events in congestive heart failure, whereas other noninvasive markers, including LP, were not.…”
Section: Twa and Arrhythmiamentioning
confidence: 89%
“…3-5, 9, 10) Although Adachi, et al 9) have reported that the presence of TWA is significantly associated with VT in patients with DCM, no studies have documented this result prospectively. Recently, Klingenheben, et al 10) reported the usefulness of TWA in the setting of congestive heart failure including use of antiarrhythmic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] However, little information is available regarding the clinical significance of TWA and QTD in the setting of DCM. [9][10][11][12] Moreover, these markers have not been prospectively compared to each other for patients with DCM. In the present study, we prospectively compared the clinical significance of TWA and QTD to identify patients at risk for ventricular tachyarrhythmias (VTs) in the setting of DCM.…”
mentioning
confidence: 99%
“…This study included patients with nonischemic dilated cardiomyopathy, and a number of other small studies have confirmed the prognostic significance of TWA in such patients. [42][43][44] An example of a positive TWA tracing in a patient with heart failure is shown in Figure 2.…”
Section: Clinical Studiesmentioning
confidence: 99%